1996
DOI: 10.1002/jor.1100140317
|View full text |Cite
|
Sign up to set email alerts
|

In vitro activation of human fibroblasts by retrieved titanium alloy wear debris

Abstract: Titanium-aluminum-vanadium wear particles isolated from the soft-issue membrane of a failed total hip arthroplasty were added to human fibroblasts in cell culture. The cellular response to particle challenge was determined by assaying for levels of interleukin-1 beta, interleukin-6, tumor necrosis factor-alpha, prostaglandin E2, basic fibroblast growth factor, platelet-derived growth factor-AB, and transforming growth factor-beta. Collagenase and gelatinase activities were analyzed by zymography and [3H]collag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
41
3

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 38 publications
8
41
3
Order By: Relevance
“…With regard to aseptic loosening, IL-1, TNF and IL-6 have all been identified in periprosthetic tissues surrounding loose implants (Chiba et al 1994, Horikoshi et al 1994. Several studies have shown that these cytokines are released from wear particle-stimulated macrophages and fibroblastic cells (Glant et al 1993, Haynes et al 1993, Manlapaz et al 1996. Strong expression of gp130 was shown on arthroplasty macrophages, FBGCs and osteoclasts in this study.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…With regard to aseptic loosening, IL-1, TNF and IL-6 have all been identified in periprosthetic tissues surrounding loose implants (Chiba et al 1994, Horikoshi et al 1994. Several studies have shown that these cytokines are released from wear particle-stimulated macrophages and fibroblastic cells (Glant et al 1993, Haynes et al 1993, Manlapaz et al 1996. Strong expression of gp130 was shown on arthroplasty macrophages, FBGCs and osteoclasts in this study.…”
Section: Discussionsupporting
confidence: 69%
“…Cytokines such as interleukin-l( (IL-l), tumor necrosis factor ( (TNF) and interleukin-6 (IL-6) are potent stimulators of osteoclastic bone resorption (Bertolini et al 1986, Gowen and Mundy 1986, Black et al 1991 and have been identified in the arthroplasty pseudomembrane that surrounds failed implants (Chiba et al 1994, Horikoshi et al 1994. In vivo and in vitro studies have shown that these cytokines are released from wear particle-stimulated macrophages and fibroblastic cells (Glant et al 1993, Haynes et al 1993, Jiranek et al 1993, Manlapaz et al 1996. The osteoclast is a highly specialized multinucleated cell which is responsible for bone resorption.…”
mentioning
confidence: 99%
“…They are abundant in the periprosthetic membranes that surround failed implants, and have been shown to phagocytize particles and respond by increasing the secretion of cytokines and proteases that are associated with enhanced bone resorption and the degradation of extracellular bone matrix [32,34].…”
Section: Introductionmentioning
confidence: 99%
“…Volume 472, Number 12, December 2014 Biological Reactions to Byproducts of Wear 3701 periprosthetic environment and their possible contribution to inflammatory osteolysis [12,47,53,62,76]. Other cells of potential interest in the pathology of debris-induced osteolysis include osteoclasts [28,58,60], osteoblasts [71], lymphocytes [7], and mesenchymal cells [62].…”
Section: Search Strategy and Criteriamentioning
confidence: 99%